2019
DOI: 10.18176/jiaci.0378
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to Shrimp Including Severe Anaphylaxis in Mite- and Cockroach-Allergic Patients Who Have Never Eaten Shrimp: Clinical Significance of IgE Cross-Reactivity to Tropomyosins From Different Sources

Abstract: Shrimp was obtained from the sea by fisherman, who were instructed to not add any additives and to place the shrimp at -20oC immediately after catching. Shrimp was kept at -20oC, and at the time of use, shrimp was thawed, had their shell removed, and boiled in water for 10 minutes.For the double-blind-placebo-controlled shrimp challenge, shrimp was crushed using a food processor, and added to a mixture of hazelnut cream, oat flakes, milk-based ice cream with small bits of chocolate, powdered chocolate and vani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Tropomyosins from HDM have significant homology with tropomyosins from different species and are frequently characterized as involved in the cross-reactivity between mites, shrimp, insects, and helminths [26,28,29,34,47,48,72]. A study in Brazil found patients who were highly IgE-reactive to shrimp tropomyosin but had never eaten shrimp or other crustaceans [73]. This study showed how tropomyosins are conserved and relevant in the cross-reactivity process.…”
Section: Discussionmentioning
confidence: 70%
“…Tropomyosins from HDM have significant homology with tropomyosins from different species and are frequently characterized as involved in the cross-reactivity between mites, shrimp, insects, and helminths [26,28,29,34,47,48,72]. A study in Brazil found patients who were highly IgE-reactive to shrimp tropomyosin but had never eaten shrimp or other crustaceans [73]. This study showed how tropomyosins are conserved and relevant in the cross-reactivity process.…”
Section: Discussionmentioning
confidence: 70%
“…This grouping may be related to the phenomenon of antigen crossing. 26 The cockroach-positive rate of AR patients in China is highest in the south, 27 followed by the east (the cockroach-positive rate of AR was lowest in the north). The reported overall positive rate was 19.37%, which is similar to that reported here.…”
Section: Discussionmentioning
confidence: 99%